Concepts of madness in diverse settings: a qualitative study from the INTREPID project. (2016)
Background: In order to facilitate case identification of incident (untreated and recent onset) cases of psychosis and controls in three sites in India, Nigeria and Trinidad, we sought to understand how psychoses (or madness) were conceptualized locally. The evidence we gathered also contributes to a long history of research on concepts of madness in diverse settings. Methods: We conducted focus group discussions and individual interviews to collect information about how informants in each site make sense of and respond to madness. A coding framework was developed and analyses of transcripts from the FGDs and interviews were conducted. Results: Analyses suggest the following: a) disturbed behaviors are the primary sign of madness; b) madness is attributed to a wide range of causes; and, c) responses to madness are dictated by cultural and pragmatic factors. These findings are congruent with similar research that has been conducted over the past 50 years. Conclusions: The INTREPID research suggests that concepts about madness share similar features across diverse settings: a) terms for madness are often derived from a common understanding that involves disruptions in mental processes and capacities; b) madness is recognized mostly by disruptive behaviours or marked declines in functioning; c) causal attributions are varied; and, d) help-seeking is a complex process.